Ð¢ÐµÑ…Ð½Ð¾Ð»Ð¾Ð³Ñ–Ñ‡Ð½Ñ– Ð¿Ñ–Ð´Ñ…Ð¾Ð´Ð¸ Ð´Ð¾ ÐºÑ€Ñ–Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²ÑƒÐ²Ð°Ð½Ð½Ñ Ð±Ñ–Ð¾ÑÐµÐ½ÑÐ¾Ñ€Ñ–Ð² Ð½Ð° Ð¾ÑÐ½Ð¾Ð²Ñ– Ñ„ÐµÑ€Ð¼ÐµÐ½Ñ‚Ñ–Ð² - Nardid, Oleg A.; Mangasarov, Dmitriy O.; Schetinskiy, Miroslav I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
Basing on the proposed approaches for storage of enzyme-based biosensors a technological process was developed, which allowed rapid and easy freezing, storage and warming of these devices. To do this we designed and produced the samples of containers, holder-cassettes, equipment for freezing according to the needed regimens. The produced equipment was involved to creation of technology for long-term storage of miniature glucose oxidase-based electrochemical biosensors.